Assessing the risk of light reduction from natural sediment resuspension events and dredging activities in an inshore turbid reef environment. (September 2021) - Luter, Heidi M.; Pineda, Mari-Carmen; Ricardo, Gerard; Francis, David S.; Fisher, Rebecca; Jones, Ross
Abstract: The reduction in benthic light from natural sediment resuspension events, dredging activities and clouds was quantified over multiple time periods (days to weeks) from a 3-year in-situ field study in the inshore turbid-zone coral communities of the Great Barrier Reef. The results were then used to examine the tolerance levels of three coral species and a sponge to light reduction and associated changes in spectral light quality (in conjunction with elevated sediment concentrations) in a 28-day laboratory-based study. All species survived the exposures but sub-lethal responses involving changes in pigmentation, lipids and lipid ratios were observed. A pocilloporid coral was the most sensitive taxon, with a 28-d EC10 value for bleaching (dissociation of the symbiosis) of 2.7 mol photons m 2 d −1 . The possibility of such light reduction levels occurring naturally and/or during maintenance dredging activities was then examined using the 3-year in-situ field study as part of a risk assessment. Highlights: Inshore corals naturally experience periods of low light impacting their physiology. Sensitive pocilloporid corals could potentially be used as an indicator of low light effects. Dredging programs should include measurements of light availability as a key pressure-parameter.